A structural analysis method for the promotion of Mexico City´s integral plan of mobility. Issue 1 (1st January 2020) - Chatziioannou, Ioannis; Alvarez-Icaza, Luis; Bakogiannis, Efthimios
Abstract: Transportation system and its Urban Transportation Infrastructure (UTI) influence an area´s economic health and quality of life because they provide the background in order the people to perform their everyday activities. Nevertheless, transportation activity generates certain negative externalities like congestion, road accidents, poor air quality that affect the people physically, emotionally and socially. These externalities become severe via the urbanization-metropolisation phenomenon that increase the distances for territorial displacement, generating major mobility demand and car usage. Consequently, an approach to urban planning is required, which would prioritize sustainable mobility. This paper's objective is to help the implementation of Integral Mobility Plans by focusing on the case of Mexico City. This can be achieved through the application of structural analysis method in two steps: first, we facilitate the identification of the interlinks among the essential urban structure's components for sustainable mobility. Second, we evaluate the effectiveness of the public policies-strategies that form part of Mexico City's Integral Mobility Plan and organize them in order of importance. The results show which UTI elements should be considered primarily for sustainable mobility and which public policies-strategies should be prioritized in order to implement the aforementioned plan effectively.